2020
DOI: 10.3390/nu12082378
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Macroalgae

Abstract: Macroalgae have attracted great interest for their potential applications in nutraceutical and pharmaceutical industries as source of bioactive medicinal products and food ingredients. This review gathers data from in vitro and in vivo studies addressing the anti-obesity effects of macroalgae. Great consensus exists in all reported in vitro studies concerning the reduction induced by seaweed extracts in the expression of transcriptional factors controlling adipogenesis. In animals, macroalgae reduced body fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…A study done on 6-week-old male C57BL/6J mice exhibited a significantly lower body weight when supplemented with 250 mg/kg body weight of C. okamurae group compared to a mouse fed with high fat diet (HFD) alone. It was observed that the weight of epididymal and perirenal adipose and the total fat of the mouse were decreased when fed with C. okamurae diet (Gómez-Zorita et al, 2020). Given these studies, it can be deduced that C. okamurae extract has the potential to prevent obesity.…”
Section: Biological Activities Of Chlorophytamentioning
confidence: 97%
See 1 more Smart Citation
“…A study done on 6-week-old male C57BL/6J mice exhibited a significantly lower body weight when supplemented with 250 mg/kg body weight of C. okamurae group compared to a mouse fed with high fat diet (HFD) alone. It was observed that the weight of epididymal and perirenal adipose and the total fat of the mouse were decreased when fed with C. okamurae diet (Gómez-Zorita et al, 2020). Given these studies, it can be deduced that C. okamurae extract has the potential to prevent obesity.…”
Section: Biological Activities Of Chlorophytamentioning
confidence: 97%
“…Given these studies, it can be deduced that C. okamurae extract has the potential to prevent obesity. This is because C. okamurae supplementation reduced the protein expressions of peroxisome proliferator-activated receptor-gamma (PPAR) and CCAAT/enhancerbinding protein alpha (C/EBP) that increased due to the HFD (Gómez-Zorita et al, 2020). Similarly, Sharma, Kim, Kim, Park, and Rhyu (2017) also highlighted the anti-obesity effect demonstrated by C. okamurae extracts.…”
Section: Biological Activities Of Chlorophytamentioning
confidence: 99%
“…Several biological properties have been associated with lipids [211,215]. Polyunsaturated fatty acids (PUFA) can benefit skin barrier protection and other biological functions can be enhanced; nutricosmetics could contribute an anti-obesity effect [211,216,217] and the regulation of inflammatory responses [25,218]. Being structural components of cell membranes, sterols regulate membrane fluidity and permeability and other properties, such as antioxidant, antiproliferative, and anti-photodamage, and antiinflammatory effects have been reported for fucosterol [28,188,[219][220][221]].…”
Section: Lipidsmentioning
confidence: 99%
“…Macroalgae metabolites have an important role because some of them can display positive effects on human health [ 10 ]. Anti-inflammatory, antitumoral, anticoagulant, antioxidant, anti-obesity and other biological properties have been associated with these macroalgae metabolites in recent research [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%